2018
DOI: 10.1111/jcmm.13535
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between myocardial fibrosis and myocardial microRNAs in dilated cardiomyopathy: A link between mir‐133a and cardiovascular events

Abstract: It is unknown whether fibrosis‐associated microRNAs: miR‐21, miR‐26, miR‐29, miR‐30 and miR‐133a are linked to cardiovascular (CV) outcome. The study evaluated the levels of extracellular matrix (ECM) fibrosis and the prevalence of particular microRNAs in patients with dilated cardiomyopathy (DCM) to investigate any correlation with CV events. Methods: Seventy DCM patients (48 ± 12 years, EF 24.4 ± 7.4%) underwent right ventricular biopsy. The control group was comprised of 7 patients with CAD who underwent CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
18
1
Order By: Relevance
“…In a separate study on 55 children affected with DCM, circulating miR-155 and miR-636 were found overexpressed, while miR-646 and miR-639 were downregulated in transplanted patients compared with affected patients who recovered their ventricular function [79]. Also, DCM was associated with altered plasma levels of miR-21, miR-26, miR-29, miR-30, miR-133a [80,81], and with the exosomal miR-92b-5p, found overexpressed in 43 affected patients [82]. Few studies have been performed on ACM, identifying miR-320a and miR-185 significantly down- and upregulated, respectively, in the plasma of affected patients [83,84].…”
Section: Circulating Mirnas As Biomarkers For Cardiac Diseasesmentioning
confidence: 99%
“…In a separate study on 55 children affected with DCM, circulating miR-155 and miR-636 were found overexpressed, while miR-646 and miR-639 were downregulated in transplanted patients compared with affected patients who recovered their ventricular function [79]. Also, DCM was associated with altered plasma levels of miR-21, miR-26, miR-29, miR-30, miR-133a [80,81], and with the exosomal miR-92b-5p, found overexpressed in 43 affected patients [82]. Few studies have been performed on ACM, identifying miR-320a and miR-185 significantly down- and upregulated, respectively, in the plasma of affected patients [83,84].…”
Section: Circulating Mirnas As Biomarkers For Cardiac Diseasesmentioning
confidence: 99%
“…Recent studies have found that miR-133a also regulates cardiomyocyte apoptosis. The expression of miR-133a was decreased in ischemic heart failure, acute myocardial ischemia-reperfusion injury model, and myocardial hypertrophy pathological model in rats [33][34][35][36]. Combined the above research with the results of this experiment, it is suggested that miR-133a-5p may be a key target for the treatment of myocardial injury induced by methamphetamine.…”
Section: Discussionmentioning
confidence: 53%
“…MiRNAs are reported to be involved in the development of DCM [35][36][37]. Among the dysregulated miRNAs, let-7i has been previously associated with poor clinical outcomes in DCM patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that miRNAs are involved in T-cell immune function and DCM pathogenesis [35][36][37]. Let-7 is reported to not only modulate T-cell function but also regulate glycolytic metabolism.…”
Section: Let-7i Regulated the Metabolic And Functional Alterations Inmentioning
confidence: 99%